Acute effects of loaded and unloaded whole-body vibration on vertical jump performance in karate athletes - Pojskic, H.; Zombra, Ž.; Washif, J.-A.; Pagaduan, J. C. (Journal of Human Kinetics, 2024)
We investigated the acute effects of different whole-body vibration (WBV) interventions on the jump height of highly trained karate practitioners. Fifteen male karate club athletes (age: 20.0 ± 3.8 years; stature: 177.3 ± 4.7 cm; body mass: 76.9 ± 11.2 kg; % body fat: 9.2 ± 4.3) performed six randomized interventions: [a] static half-squat (SHS); [b] SHS with external loads at 30% of the body weight (SHS + 30%BW); [c] WBV at frequency (f) 25 Hz, and 2 mm amplitude (A) (WBV 25/2); [d] WBV 25/2 with external loads of 30% of the body weight (WBV 25/2 + 30% BW); [e] WBV at f = 50 Hz, and A = 4 mm (WBV 50/4), and [f] WBV 50/4 with external loads of 30% of the body weight (WBV 50/4 + 30% BW). Each intervention was performed for 5 sets at 60 s/set, with a rest interval of 30 s between sets. Countermovement jump (CMJ) data were collected at 2, 4, 6, 8 and 10 min after each preconditioning intervention. Two-way repeated-measures ANOVA revealed a non-significant main effect of intervention [F(5, 10) = 1.44, ?2 = 0.42, p = 0.29)] and a significant main effect of the rest interval [F(4, 11) = 3.51, n2 = 0.56, p = 0.04)] on CMJ height. A rest interval of 4 min resulted in significantly higher CMJ values than a rest interval of 2 min (p = 0.031). In conclusion, utilizing a 4-min rest interval irrespective of the intervention schemes may have potential for enhancing jumping performance among highly trained karate athletes.